contestada

Solve the equation by completing the square

s^2+2s-6=0

s=
s=

Please answer this ASAP ! And with step by step expiation please !

Solve the equation by completing the square s22s60 s s Please answer this ASAP And with step by step expiation please class=

Respuesta :

Answer:

s = - 1 ± [tex]\sqrt{7}[/tex]

Step-by-step explanation:

Given

s² + 2s - 6 = 0 ( add 6 to both sides )

s² + 2s = 6

To complete the square

add ( half the coefficient of the s- term )² to both sides

s² + 2(1)s + 1 = 6 + 1

(s + 1)² = 7 ( take the square root of both sides )

s + 1 = ± [tex]\sqrt{7}[/tex] ( subtract 1 from both sides )

s = - 1 ± [tex]\sqrt{7}[/tex]

Thus

s = - 1 - [tex]\sqrt{7}[/tex] , s = - 1 + [tex]\sqrt{7}[/tex]

ACCESS MORE